2021
DOI: 10.26434/chemrxiv-2021-lq308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of gas-accessible microporosity in metal-organic framework glasses

Abstract: Metal-organic framework (MOF) glasses are a new class of microporous glass materials with immense potential for applications ranging from gas separation to optics and solid electrolytes. Due to the inherent difficulty to determine the atomistic structure of amorphous glasses, the intrinsic structural porosity of MOF glasses is only poorly understood. In this work, the porosity features of a series of prototypical MOF glass formers from the family of zeolitic imidazolate frameworks (ZIFs) and their correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 74 publications
(114 reference statements)
0
20
0
Order By: Relevance
“…17 ZIF-zni has also recently been reported to undergo melting at 585 °C when heated directly from room temperature. 44 However, in this study, a T g was not reported and it was noted that the resulting glass, denoted a g ZIF-zni, contained zinc oxide. 44 Here, we investigate the thermal response of ZIF-zni in detail to (i) locate its T g and, (ii) determine whether a g ZIF-zni can be prepared without zinc oxide growth.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…17 ZIF-zni has also recently been reported to undergo melting at 585 °C when heated directly from room temperature. 44 However, in this study, a T g was not reported and it was noted that the resulting glass, denoted a g ZIF-zni, contained zinc oxide. 44 Here, we investigate the thermal response of ZIF-zni in detail to (i) locate its T g and, (ii) determine whether a g ZIF-zni can be prepared without zinc oxide growth.…”
Section: Introductionmentioning
confidence: 62%
“…44 However, in this study, a T g was not reported and it was noted that the resulting glass, denoted a g ZIF-zni, contained zinc oxide. 44 Here, we investigate the thermal response of ZIF-zni in detail to (i) locate its T g and, (ii) determine whether a g ZIF-zni can be prepared without zinc oxide growth. We then go on to study how the incorporation of different linker chemistry influences melting in zni topology frameworks.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…NLDFT and Horvath–Kawazoe (HK) are inadequate, and that improvements are required in future statistical models based on CO 2 adsorption to more accurately reproduce the porosity within MOF glasses. 29…”
Section: Discussionmentioning
confidence: 99%
“…NLDFT and Horvath-Kawazoe (HK) are inadequate, and that improvements are required in future statistical models based on CO 2 adsorption to more accurately reproduce the porosity within MOF glasses. 29 Excitingly, and for the rst time, a g ZIF-62(Zn) is shown to be porous towards larger hydrocarbon gases, such as n-butane, propane, and propylene. The larger kinetic diameter of nbutane (4.3 Å) compared to CO 2 (3.3.…”
Section: Porosity In Crystalline Mofsmentioning
confidence: 99%